Sinergitas Tri Pusat Pendidikan dalam Penguatan Nilai-Nilai Pendidikan Karakter Peseta Didik - Muhammad Fauzil ‘Adzim (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2021)
Social change in society in the digital 4.0 era is an educational challenge. The Indonesian nation is being faced with the problem of the weakening of the nation's character in students. Therefore, it is necessary to carry out the values of character education in facing these educational challenges. With the synergy, the tri education center must be able to act as a shield to fortify the young generation. The purpose of this study is to describe the efforts of tri education center synergy that consists of family, school and community environment in strengthening the values of character education in the millennial era. The research method uses qualitative research carried out at Diponegoro Middle School, Depok, Sleman Regency. The results of the study are that making schools a formal pillar as mediators, while families and communities become the pillars of character education implanted in schools. The school strategies are the synergy of the school with the family, the synergy of the school with the community and the synergy of the school with the family and the community.